Biografi Gus Dur = The Authorized biography of Abdurrahman Wahid / Greg Barton; penerjemah, Lie Hua; editor, Ahmad Suaedy - BARTON, Greg; Lie Hua; Ahmad Suaedy (LKIS, 2011)
xxviii, 516 hlm. : ilus. ; 23 cm.